On Maximal Degree of Domination for Decision Making - Suhirman, .; Jasni, Mohamad Zain
This paper presents an extended decision making of soft set to multi-valued information systems. By the notion of multi-soft sets, the concept of domination between two soft sets is proposed. Then the highest value of domination is used for the best selection as a decision attribute. The technique gives an alternative solution for attribute-based decision making, instead of the best choice of object as a standard soft set in Boolean-valued information systems